Preparation of Novel 4′-Spirocyclopropyl Nucleoside Analogues - Verhoeven, Jonas; Kong, Hanchu; Zhao, Yongbin; Wang, Wenbin; Pande, Vineet; Brambilla, Marta; Van Hecke, Kristof; Meerpoel, Lieven; Thuring, Jan Willem; Verniest, Guido (Synlett, 2021)
The stereoselective preparation of a novel 4′-spirocyclopropyl nucleoside analogue has been developed by using a semibenzilic Favorskii rearrangement of a 4′-(2-chloro-3-oxocyclobutyl)spirofuranose as a key step. These chiral spirocyclic intermediates, readily obtained on a multigram scale from chiral-pool starting materials, were shown to be highly suitable precursors for achieving full stereoselectivity in the reduction–ring contraction sequence. The downstream introduction of a nucleobase through Vorbrüggen glycosylation successfully resulted in the formation of the corresponding novel 4′-spirocyclic nucleoside analogue in a stereospecific manner.
Keywords: cycloaddition; spiro compounds; rearrangement; glycosylation; nucleosides; Favorskii rearrangement